2015
DOI: 10.14348/molcells.2015.2142
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribosyl)ation of p53 Contributes to TPEN-Induced Neuronal Apoptosis

Abstract: Depletion of intracellular zinc by N,N,N′,N′-tetrakis(2-pyridylmethyl) ethylenediamine (TPEN) induces p53-mediated protein synthesis-dependent apoptosis of mouse cortical neurons. Here, we examined the requirement for poly(ADP-ribose) polymerase (PARP)-1 as an upstream regulator of p53 in zinc depletion-induced neuronal apoptosis. First, we found that chemical inhibition or genetic deletion of PARP-1 markedly attenuated TPEN-induced apoptosis of cultured mouse cortical neurons. Poly(ADP-ribosyl)ation of p53 oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
(49 reference statements)
1
5
0
Order By: Relevance
“…Chemical inhibition of the PARP‐1 function suppresses the induction of P53 in response to ionizing radiation in MCF‐7 and BJ/TERT cells [Wieler et al, ]. Based on chemical inhibitor or genetic studies, PARP‐1 acts as an upstream modulator of post‐translational modification of P53 [Kim et al, ]. These data clearly suggest that PARP‐1 is a positive regulator of P53, and our results also show that PARP‐1 deficiency results in reduced P53 levels (Fig.…”
Section: Discussionsupporting
confidence: 73%
“…Chemical inhibition of the PARP‐1 function suppresses the induction of P53 in response to ionizing radiation in MCF‐7 and BJ/TERT cells [Wieler et al, ]. Based on chemical inhibitor or genetic studies, PARP‐1 acts as an upstream modulator of post‐translational modification of P53 [Kim et al, ]. These data clearly suggest that PARP‐1 is a positive regulator of P53, and our results also show that PARP‐1 deficiency results in reduced P53 levels (Fig.…”
Section: Discussionsupporting
confidence: 73%
“…p53 activation and p53‐mediated apoptosis depend on the status of PARP‐1 and the degree of DNA strand breaks. For example, reduced p53 accumulation and activation were observed in PARP‐1 deficient cells upon treatment of N,N,N ′ ,N ′‐tetrakis(2‐pyridylmethyl)ethylenediamine (TPEN) and the alkylating agent 2′‐methyl‐2′‐nitrose‐urea (MNU) . It has been demonstrated that p53 activation transcriptionally upregulates death receptor proteins such as Fas, oncogene K‐RAS, and inhibits the antiapoptotic function of Bcl‐2, which might trigger the extrinsic pathway of apoptosis .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we investigated whether these selected agents reduced the apoptosis when exposed to the following: (1) N , N , N ′, N ′-tetrakis­(2-pyridylmethyl)­ethylenediamine (TPEN), a cell-permeant zinc chelator; (2) etoposide (ETPS), a topoisomerase II inhibitor; or (3) staurosporine (STSP), a potent cell-permeable inhibitor of various protein kinases (Figure C). Although STSP-induced apoptosis was attenuated by five compounds (1A09, 1D08, 1H10, 2G11, and 3A02) and by Cpd C (Figure C, right graph), agents 1H10 and 2G11 treatment protected from apoptosis in all three experimental conditions (Figure C).…”
Section: Results and Discussionmentioning
confidence: 99%